2022
DOI: 10.3389/fonc.2021.756246
|View full text |Cite
|
Sign up to set email alerts
|

Seven Genes Associated With Lymphatic Metastasis in Thyroid Cancer That Is Linked to Tumor Immune Cell Infiltration

Abstract: ObjectiveSince there are few studies exploring genes associated with lymphatic metastasis of thyroid carcinoma (THCA), this study was conducted to explore genes associated with lymphatic metastasis of THCA and to investigate the relationship with immune infiltration.MethodsDifferentially expressed genes associated with THCA lymphatic metastasis were analyzed based on The Cancer Genome Atlas Program (TCGA) database; a protein-protein interaction(PPI)network was constructed to screen for pivotal genes. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…This may be related to the fact that TIMP 1 antagonizes the overexpression of MMPs in UC and inhibits the involvement of MMPs in the shaping of the inflammatory microenvironment in UC [ 52 ]. In terms of immune cells, Wu believes that TIMP1 is a key gene involved in the infiltration of immune cells in thyroid cancer lymphatic metastasis [ 53 ]. TIMP1 potently inhibits the polarization of NK cells toward a decidual-like phenotype [ 54 ] and increases hepatic neutrophil infiltration [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the fact that TIMP 1 antagonizes the overexpression of MMPs in UC and inhibits the involvement of MMPs in the shaping of the inflammatory microenvironment in UC [ 52 ]. In terms of immune cells, Wu believes that TIMP1 is a key gene involved in the infiltration of immune cells in thyroid cancer lymphatic metastasis [ 53 ]. TIMP1 potently inhibits the polarization of NK cells toward a decidual-like phenotype [ 54 ] and increases hepatic neutrophil infiltration [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…CCL2, also known as the inflammation-associated expression signature, was mostly derived from cancer-associated fibroblasts, which were components of the cholangiocarcinoma tumor microenvironment. [ 16 , 17 ] Its risk score in the total population was significantly related to OS (HR = 3.144, 95% CI = 1.908–5.178, P < 0.001). Multivariate Cox analysis demonstrated that the risk score remained an independent predictor of OS after controlling for additional confounding variables (HR = 2.792, 95% CI = 1.651–4.721, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the expression of ERBB2 was found to be positively correlated with VEGF-associated genes of VEGFA , FLT , KDR , and FLT4 ( Shibuya, 2011 ), vascular endothelial cell markers of PECAM1 and VWF ( Bauer et al, 2015 ), and vascular support-related genes of TEK , ANGPT1 , ANGPT2 , CDH5 , CLDN5 , and JAM2 ( Oshi et al, 2021 ). Furthermore, the expression of ERBB2 was positively correlated with lymph node metastatic signature genes such as EVA1A , TIMP1 , SERPINA1 , FAM20A , FN1 , TNC , and MXRA8 ( Wu et al, 2021 ), and distant metastatic signature genes of MMP2 , PTTG1 , VEGFC , CXCR4 , and FGF2 ( Liang et al, 2011 ). Besides, ERBB2 expression was also positively correlated with proliferation-related genes, such as MKI67 , PCNA , and MCM2 ( Juríková et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Co-expression heat map assesses the correlation between the expression of ERBB2 and gene sets, including the iodine metabolism-related gene set of TSHR , SLC5A8 , SLC26A4 , and TPO ( Portulano et al, 2013 ), the tumor angiogenesis gene set of VEGFA , FLT1 , KDR , FLT4 , PECAM1 , VWF , TIE1 , TEK , ANGPT1 , ANGPT2 , CDH5 , and CLDN5 ( Smith et al, 2010 ; Haibe et al, 2020 ), Lymph node metastasis gene set of EVA1A , TIMP1 , SERPINA1 , FAM20A , FN1 , TNC , and MXRA8 ( Wu et al, 2021 ), distant metastatic gene sets of MMP2 , PTTG1 , VEGFC , CXCR4 , and FGF2 , tumor cell proliferation set of MKI67 , PCNA , and MCM2 ) ( Liang et al, 2011 ), and MEKi resistance marker gene set of SPRY2 , SPRY4 , ETV4 , ETV5 , DUSP4 , DUSP6 , CCND1 , EPHA2 , and EPHA4 ( Mazzoni et al, 2019 ; Degirmenci et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%